(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The digital ruble, as a new digital means of payment, has the potential to become a driver of digitalization of the Russian economy. The article examines the role of the digital ruble in stimulating digital transformation processes in various sectors of the economy. The main advantages and possible risks associated with the introduction of the digital ruble are analyzed, and its impact on the development of digital technologies and financial innovations in the country is assessed. In the context of the gradual introduction of the digital ruble, recommendations are offered on the optimal use of this digital currency in order to stimulate the digitalization of the economy and increase the competitiveness of Russian companies in the global market.